2014
DOI: 10.1111/1750-3841.12707
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Dynamics of Salted and Fermented Shrimp based on Denaturing Gradient Gel Electrophoresis

Abstract: The Korean traditional seafood jeotgal is consumed directly or as an additive in other foods to improve flavor or fermentation efficiency. Saeujot, made from salted and fermented tiny shrimp (SFS; Acetes japonicus), is the best-selling jeotgal in Korea. In this study, we reveal the microbial diversity and dynamics in naturally fermented shrimp by denaturing gradient gel electrophoresis (DGGE). The population fingerprints of the predominant microbiota and its succession were generated by DGGE analysis of univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…Most types of jeotgal are made simply by mixing the raw materials with salt and preserving them for several months before consumption [1]. Various microorganisms have been isolated from jeotgal, and identified by cultural methods and/or culture-independent methods [2][3][4][5][6]. Due to the high salinity of most jeotgal types (20-30%, NaCl), halophilic and halotolerant microorganisms can grow during jeotgal fermentation, and they are believed to contribute to the development of the varied and unique flavors of jeotgal.…”
Section: Introductionmentioning
confidence: 99%
“…Most types of jeotgal are made simply by mixing the raw materials with salt and preserving them for several months before consumption [1]. Various microorganisms have been isolated from jeotgal, and identified by cultural methods and/or culture-independent methods [2][3][4][5][6]. Due to the high salinity of most jeotgal types (20-30%, NaCl), halophilic and halotolerant microorganisms can grow during jeotgal fermentation, and they are believed to contribute to the development of the varied and unique flavors of jeotgal.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, information regarding microbial diversity of the shrimp paste products is scarce compared to that of other products (i.e., fermented dairy and soybean products). Recently, Han et al (2014) described the microbial dynamics and succession during the fermentation of Jeotgal, a Korean fermented shrimp. Using the denaturing gradient gel electrophoresis technique, they found that a diverse group of bacteria was present in which the members of the order Bacillales were predominant (Han et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…However, the Proteobacteria members are found at the beginning and replaced by those of the Firmicutes during the fermentation (Lee et al 2014). Han et al (2014) also pointed out that the bacterial members of the order Bacillales are predominant during Saeujot's fermentation. The incidence of this particular bacterial group is expected considering from the selective condition provided for the shrimp paste fermentation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, characterization of microbial communities is important for providing objective quality indices to determine shelf life in seafood. For instance, the microflora of processed (chilled, cooked, peeled, packed, salted and fermented) shrimp has been largely studied using selective culture media (Mejlholm et al, 2005;Laursen et al, 2006;Han et al, 2014). Culture-independent methods are also being increasingly used to develop a complete overview of the bacterial community characteristics.…”
Section: Introductionmentioning
confidence: 99%